PERS DAN REPRESENTASI CITRA PEREMPUAN DALAM POLITIK (ANALISIS WACANA PEMBERITAAN POLITISI PEREMPUAN INDAH DHAMAYANTI PUTRI DI HARIAN LOMBOK POST DAN SUARA NTB PERIODE - DIYAH INDIYATI; Hartin Nur Khusnia; Dian Lestari Miharja (Universitas Mataram, 2018)
The mass media fact report within social reality comes with a complexities of interest. As an institution which has the power to shape public opinion, the press also able to give influence both positive and negative, depend on the interests represented. Including while representing the image of women in politics through its news report. Through the news report, text media construct a reality of a women in politics image. In which this reality constructed by the media is not a value-free.This study analyses the media discourse of a woman politician recently elected as a Bupati (which has the same rank as a Mayor) of Bima District Indah Dhamayanti Putri in the local news media coverage Lombok Post and Suara NTB from the February to May 2016. Both newspaper are daily newspaper which contribute the largest circulation in the province of West Nusa Tenggara. Hence, the two media are the most accessed printed media in the province. How the reality of woman leadership in local scale constructed by this two dailies will certainly influence the view of the people , and the way people behave towards this leadersship. Moreover Indah Dhamayanti Putri is the first female leader in the province of West Nusa Tenggara.The news about Indah Dhamayanti Putri leadership analyzed in this study consist of her profile as the Bupati, her political activities, polocies and programs. The news analyzed using critical discourse analysis method from Norman Fairclough model, by analyzing the text in the macro-micro societal context. FOcus of the analysis are more on how language is formed and shaped from social relationships and a certain social context. Fairclough divide discourse analysis in three dimensions, textual analysis, discourse practice and socio-cultural practices . From the research conducted, it appears that women politicians Indah Dhamayanti Putri are perceived in terms of stereotypes both in terms of physical appearance, figure or her role as wife and mother are still inherent in the discourse of textual reports of two mass media. Keywords: Representation women politician, image, discourse analysis